Acoustic analysis assessment in speech pathology detection - Panek, Daria; Skalski, Andrzej; Gajda, Janusz (1933- ); Tadeusiewicz, Ryszard (1947- ) (Zielona Góra: Uniwersytet Zielonogórski)
Automatic detection of voice pathologies enables non-invasive, low cost and objective assessments of the presence of disorders, as well as accelerating and improving the process of diagnosis and clinical treatment given to patients.
Keywords: linear PCA; non-linear PCA; auto-associative neural network; validation; voice pathology detection